REDESAIN MEJA SIRKULASI PERPUSTAKAAN UNIVERSITAS SURABAYA - Adi Gunawan Kwan; Elieser Tarigan; Wyna Herdiana (CALYPTRA, 2018)
A container for a university to have the purpose of providing services to students of University of Surabaya in addition to boost the productivity of the workers themselves. The Sirkulasi desk is one of the parts in the library on the table itself is doing a lot of important activities such as collecting out the books borrowed by students. However, the library Sirkulasi table that is currently lacking needs with the understanding of the user itself. Given the library of the University of Surabaya has been since 1995 where the world increasingly changed as well as lifestyle pemustaka. Formerly the internet is no longer developing today that can be accessed almost anywhere. With the current internet, look at the library as it began to be forgotten. How to change the design becomes an important thing that needs to be done for the function. Knowing the modern lifestyle continues to grow rapidly, conducted various observations and interviews to find out the design concept that will be implemented on the private table that will be redesigned to be realized into a prototype to boost something that is in the processThe purpose of this research is to design the circulation table for workers and students of University of Surabaya Library as an effort to improve the performance and productivity of workers and students. In research on this design method used is qualitative method that is IDI on some putskawan and some student which is in Library of Universtas Surabaya, And Observation which done by observing Activity Study done at circulation table. From the results of research that will be designed table of circulation in the area of the Library to meingkatakan Productivity of the workers own advantages that is, the new form with the concept of Futursitik, but now it has a larger workplace and equipment arranged that simplify the workmanship.